2020
DOI: 10.20290/estubtdb.706641
|View full text |Cite
|
Sign up to set email alerts
|

In the Context of Time-Independent Parameters in Two Quantum Systems: Quantum Entanglement and Correlations With Negativity Measurement

Abstract: In this paper, we consider two phonons and three-level trapped ion in configuration forming Hilbert 12-space. The negativity and quantum correlations are revealed in trapped ion two phonon states system. Three values of LDP, = 0.006, =0.06 and =0.08 are given. The effects of the time-independent coupling in terms of the system, degree of quantum entanglement are investigated. Therefore, we have found the main optimal times for obtaining the high amount of entanglement with negativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…In line with of the measures and the results reported above, we observed that the maximally entangled states do not collapse in the TRIcoherent system. We examined with S that the measurement degrees have a sudden appearance of the entangled state in parallel with raising η, which is in agreement with previous observations [21,[28][29][30]. The article in Ref.…”
Section: Fidelity Quantum Entropy and Discussionsupporting
confidence: 90%
“…In line with of the measures and the results reported above, we observed that the maximally entangled states do not collapse in the TRIcoherent system. We examined with S that the measurement degrees have a sudden appearance of the entangled state in parallel with raising η, which is in agreement with previous observations [21,[28][29][30]. The article in Ref.…”
Section: Fidelity Quantum Entropy and Discussionsupporting
confidence: 90%